Hemoglobin induces inflammation through NF-kB signaling pathway and causes cell oxidative damage in grass carp (Ctenopharyngodon idella) - Tang, Ying; Yang, Shiyi; Yao, Minshan; Yang, Minxuan; Wei, Lixiang; Chen, Hong; Lin, Junyan; Huang, Yao; Lin, Li; Qin, Zhendong (Frontiers in Immunology, 2022)
Hemolytic disease in grass carp (C. idella) leads to hemolysis in vivo, releasing damage-related molecular patterns (DAMPs) hemoglobin (Hb; which is rapidly oxidized to Hb-Fe3+ and Hb-Fe4+) and generating a high level of reactive oxygen species (ROS) that cause oxidative damage. However, the effect of cell-free Hb on tissue cells of grass carp has yet to be elucidated. In this study, western blotting (WB) and immunofluorescence analysis (IFA) results showed that PHZ-induced hemolysis caused Hb and iron accumulation, increased the production of ROS and resulted in apoptosis in head kidney and middle kidney of the grass carp. Quantitative real-time PCR (qRT-PCR), WB, and IFA revealed that PHZ-induced hemolysis significantly upregulated the expression of inflammation-related genes through activation of the NF-κB signaling pathway. To further explore the effect of Hb, three forms of Hb (Hb, MetHb, and FerrylHb) were prepared. The incubation with the different forms of Hb and heme markedly upregulated the expression of cytokine genes through NF-κB signaling pathway, which was further confirmed by a specific inhibitor (caffeic acid phenethyl ester, CAPE). Flow cytometry analysis data showed that the stimulation of different forms of Hb and heme increased the production of ROS, and resulted in apoptosis. In summary, our data suggest that the excess cell-free Hb released during hemolysis modulates the inflammatory response through activation of the NF-κB signaling pathway and causes cell oxidative damage and apoptosis.